Can SARS-CoV-2 Viral RNA Continually Persist in an Asymptomatic COVID-19 Patient? - Sen Variaveettil Thomas; Anjala Nizam; Tarab Iqbal (Dubai Medical Journal)
An asymptomatic 39-year-old male patient with well-controlled hypertension on a combination of antihypertensives including angiotensin receptor blocker was screened positive for SARS-CoV-2 by RT-PCR nasopharyngeal (NP) swab and was admitted to an isolation facility in Dubai on March 23, 2020. He had a history of exposure to a COVID-19 patient a few days prior to the screening test. His chest X-ray showed signs of pneumonitis. He was discharged from the isolation facility on day 28 with 2 consecutive negative SARS-CoV-2 RT-PCR NP swab results, 24 h apart. After 14 days of home quarantine, he tested positive again for SARS-CoV-2 on day 44 and was again isolated in our facility. He continued testing positive until day 51, after which he was discharged again following 2 consecutive negative tests 24 h apart.